2012
DOI: 10.4067/s0718-19572012000100012
|View full text |Cite
|
Sign up to set email alerts
|

Dental abnormalities of the southern thorny skate Amblyraja doellojuradoi (Chondrichthyes, Rajidae)

Abstract: Abstract.-Teeth morphology has been widely used in taxonomic, biological and fossil teeth studies of Chondrichthyes. Herein, dental abnormalities in Amblyraja doellojuradoi are described. Almost 10% of 182 specimens sampled presented any of these types of dental anomalies: (1) an additional incomplete tooth row between two complete rows, (2) an increasing tooth base size and division of its cusps until the complete splitting of teeth in the same row, and (3) an irregular tooth arrangement on the right side of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Generally, species that consume fish have sharp teeth to capture these prey items more successfully (Feduccia & Slaughter, 1974). However, teeth of A. doellojuradoi were sharper in males than in females, in opposition to the difference reported in diet (Delpiani et al , 2012). Thayer et al (1973) proposed that prey consumption is determined by the calorific value.…”
Section: Discussionmentioning
confidence: 57%
“…Generally, species that consume fish have sharp teeth to capture these prey items more successfully (Feduccia & Slaughter, 1974). However, teeth of A. doellojuradoi were sharper in males than in females, in opposition to the difference reported in diet (Delpiani et al , 2012). Thayer et al (1973) proposed that prey consumption is determined by the calorific value.…”
Section: Discussionmentioning
confidence: 57%
“…Most dental studies have focused mainly on brief and incomplete descriptions of the external and internal morphology of the teeth and are restricted to reports of the number of teeth, arrangement and absence or presence of dental sexual dimorphism (Feduccia & Slaughter, ; Du Buit, ; Sáez & Lamilla, , ). A previous, qualitative analysis of the dentition of A. doellojuradoi showed that this species has a gradient monognathic heterodonty (Delpiani et al ., ), meaning that there is a gradual variation in the tooth morphology along the parallel axis of the jaw. Amblyraja radiata has the same sort of dentition, according to the description given by Herman et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the south‐west Atlantic Ocean Amblyraja doellojuradoi (Pozzi 1935) is the most common species of its genus, but little is known of its biology so far. Only recently have there been analyses of its diet (Delpiani et al ., ), reproduction (Delpiani, ) and particular dental anomalies (Delpiani et al ., ). The last study includes a brief qualitative description of the dentition, finding that A. doellojuradoi has a gradient monognathic heterodonty.…”
Section: Introductionmentioning
confidence: 99%
“…the Zearaja and Dipturus complex (Last & Gledhill, 2007). Recently, a comprehensive study of the clasper in three Amblyraja species have been published (Delpiani et al, 2012) contributing to enhance the species diagnosis as a major component of genus morphology.…”
Section: Distributionmentioning
confidence: 99%
“…Structural consistencies can be detected in the clasper internal cartilages within A. frerichsi and A. doellojuradoi, A. hyperborea (Collett 1879) and A. radiata (Donovan 1808) (Stehmann, 1970;Hulley, 1972;Delpiani et al, 2012); especially in the shape of the dorsal terminal 2 (dt2) and 4 (dt4); the ventral terminal and the accessory terminal 1 (at1) and 2 (at2) cartilages. But the shape and disposition of dorsal terminal 1 (dt1) and 2 (dt2) cartilages are slightly different; and these differences together may be used in the species diagnosis.…”
Section: Distributionmentioning
confidence: 99%